A 3.3-MHz fast-response load-dependent-on/off-time buck-boost DC-DC converter with low-noise hybrid full-wave current sensor. (April 2018) - Wang, Zhao; Chen, Biao; Zhu, Lei; Zheng, Yanqi; Guo, Jianping; Chen, Dihu; Ho, Marco; Leung, Ka Nang
Abstract: A 3.3-MHz current mode control buck-boost DC-DC converter is proposed in this work. Composed of comparator control and load-dependent on/off time modulation technique, the converter can achieve a faster load transient response by reducing the delay from 2.7 μs to 1.5 μs during constant on/off time. Thus, the comparator can take effect faster. To fulfill a fixed frequency operation to reduce electromagnetic interference (EMI), a frequency controller locks the switching frequency to 3.3 MHz. Also, a hybrid full-wave current sensor is proposed to achieve current mode control. The proposed hybrid current sensor inherits good AC performance from a filter-based current sensor and good DC performance from a SenseFET-based one. As a result, state switching between high-side sensing and low-side sensing will not induce large spiking on the current sensor output. Moreover, the DC accuracy of current sensing will not be affected by the DC resistance (DCR) of the inductor. Highlights: Load-dependent on/off-time modulation technique is proposed to alleviate the delay in traditional constant on/off-time modulator from 2.7 μs to 1.5 μs. A hybrid full-wave current sensor is proposed to achieve accurate current sensing and low noise performance. A comparator-based buck-boost converter is implemented to verify the load-dependent on/off-time modulator and full-wave current sensor. Switching frequency of 3.3 MHz is achieved in the converter by the assistance of a frequency controller. The peak efficiency values for buck, buck-boost, and boost modes are 92.5%, 94.7% and 94.7% respectively.